Normalization of left ventricular filling pressure after cardiac surgery for the Loeffler's endocarditis: a case report. Issue 6 (28th June 2021) - Carcaterra, Andrea; Mock, Stéphane; Müller, Hajo; Testuz, Ariane
Abstract: Background: Loeffler endocarditis is a rare restrictive cardiomyopathy, characterized by hypereosinophilia and fibrous thickening of the endocardium causing progressive onset of heart failure and appearance of thrombi on the walls of the heart chambers. Case summary: A 72-year-old man known for hypertension and dyslipidaemia consults for progressive dyspnoea up to New York Heart Association (NYHA) Classes 2–3 over 3 weeks. The biological balance sheet shows a high eosinophil level and an echocardiography shows a mild echodensity fixed to the left apex. After exclusion of a secondary cause of hypereosinophilia, diagnosis of endomyocardial fibrosis in the context of a hypereosinophilic syndrome (HES) is therefore retained. The patient's clinical presentation with cardiac involvement leads us to start a treatment with corticosteroids. The patient is then regularly followed every 6 months with an initially stable course without complications. Two years later, he develops progressive signs of heart failure. Transthoracic echocardiography shows a left ventricular (LV) dilatation with a normal ejection fraction, but decreased volume due to a large echodense mass in the apex, and moderate aortic regurgitation caused by myocardial infiltration. In view of this rapid evolution, resection of the LV mass with concomitant aortic valve replacement is performed. Pathology confirms eosinophilic infiltration. The clinical course is very good with a patient who remains stable with dyspnoea NYHA Classes 1–2, and echocardiography at 1 year shows a normalization of LV filling pressure. Discussion: HES represents a heterogeneous group of disorders characterized by overproduction of eosinophils. One of the major causes of mortality is associated cardiac involvement. Endocardial fibrosis and mural thrombosis are frequent cardiac findings. Echocardiography plays a crucial role in initial diagnosis of endomyocardial fibrosis, and for regular follow-up in order to adapt medical treatment and monitor haemodynamic evolution of the restrictive physiology and of valvular damage caused by the disease's evolution. This case also shows that surgery can normalize filling pressure and allow a clear improvement on the clinical condition even at the terminal fibrotic state.